1998
DOI: 10.2214/ajr.171.4.9762979
|View full text |Cite
|
Sign up to set email alerts
|

Vascular leiomyoma of an extremity: MR imaging-pathology correlation.

Abstract: OBJECTIVE. The objectiveof our studywas to analyzeMR imagesof vascularleiomy oma of the extremity and to compare these images with histopathologic findings to determine if a correlation exists. CONCLUSION. T2-weightedMR imagesof vascular leiomyomaof anextremityshowedamass with mixed areas that were both hyper-and isointense to skeletal muscle and also revealed a hypointense rim; these images correlate with histopathologic findings of smooth muscle, vessels, fibrous tissue, an intravascular thrombus, and a fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
73
4
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 6 publications
5
73
4
4
Order By: Relevance
“…However, as presented in our case, at US the lesion usually appears hypoechoic, clivated from the tendons, but MR can better delineate the lesion and define its relationship to the adjacent structures allowing a better pre-excisional planning [5]. Hwang et al [6] found that the smooth muscle and numerous vessels within vascular leiomyomas corresponded to hyperintense areas on T2-weighted MR images. In addition, the fibrous capsule was identified as a well-defined peripheral hypointense area on T2-weighted MR.…”
Section: Discussionmentioning
confidence: 59%
“…However, as presented in our case, at US the lesion usually appears hypoechoic, clivated from the tendons, but MR can better delineate the lesion and define its relationship to the adjacent structures allowing a better pre-excisional planning [5]. Hwang et al [6] found that the smooth muscle and numerous vessels within vascular leiomyomas corresponded to hyperintense areas on T2-weighted MR images. In addition, the fibrous capsule was identified as a well-defined peripheral hypointense area on T2-weighted MR.…”
Section: Discussionmentioning
confidence: 59%
“…Hwang's group reported that diŠerential diagnosis of schwannoma is not easy because of the well deˆned capsules and mixed signal intensities. 7 Stoller and associates also reported that hypervascular tumors had quite similar characteristics, even though hemangiopericytomas and some hemangiomas are often characterized by the presence of serpiginous vessels and a slight hyperintensity on T1-weighted images. 10 Because the tumors in both of our cases were hypervascular and larger than any previously reported, they had to be distinguished from malignant tumors, for example, from malignantˆbrous histiocytoma or hemangiopericytoma.…”
Section: Discussionmentioning
confidence: 91%
“…Hwang's group compared MR images of vascular leiomyomas of an extremity with histopathologicˆndings in 4 patients. 7 The smooth muscle and numerous vessels corresponded to the hyperintense areas on T2-weighted MR images, and the toughˆbrous tissue appeared isointense to skeletal muscle on T2-weighted MR images. On the T2-weighted images, the appearance was variable, probably caused by the vessels, revealing a myxomatousˆbrous content.…”
Section: Discussionmentioning
confidence: 93%
“…9-12 Hwang et al 10 suggested that the smooth muscle and the numerous vessels corresponded to the high signal intensity areas, while the fibrous tissue appeared iso signal intensity on T2-weighted MR images. Yoo et al 11 suggested that the presence of tortuous vascular channels surrounded by smooth muscle bundles and areas of myxoid change could explain the heterogenicity of signal intensity of the tumor on T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%